Social capital on mobile SNS addiction: A perspective from online and offline channel integrations. Issue 4 (1st August 2016) - Yang, Shuiqing; Liu, Yuan; Wei, June
Abstract : Purpose: – Social capital has been identified as a valuable resource that can lead to various positive outcomes of social activities in both online and offline communities. The purpose of this paper is to argue that social capital can also be an important ingredient in the development of adverse outcomes, such as technology addiction. Design/methodology/approach: – Based on social capital theory and prior research related to perceived integration, a research model that reflects the effects of online and offline social capitals as well as perceived integration on mobile social networking service (SNS) addiction was developed and empirically examined based on data collected from 458 mobile SNS users in China. Findings: – The structural equation modeling analysis shows that online social interaction ties and online social supports positively affect mobile SNS addiction, whereas offline social supports and online social identification negatively affect mobile SNS addiction. In addition, perceived integration between online and offline channels by using mobile SNS positively influences online social interaction ties, offline social interaction ties, and mobile SNS addiction. Practical implications: – From the practical perspective, the results of the study offer interesting implications for managing mobile SNS addiction. The study found that online social interaction ties and online social support positively influence mobile SNS addiction, whereas offline social support negatively influence mobile SNS addiction. Social implications: – The mobile SNS users should invest more time to participate in offline social activities and maintain good social relationships with their family, colleagues, and friends in the real world. Originality/value: – The present study has both theoretical and practical implications. From a theoretical perspective, unlike many previous studies tend to regard social capital as the predictor of positive outcomes of users' social activities, the study contributes to the extant information systems literature by exploring the potential negative consequences of social capital on users' social lives. The results of the study indicate that social capital is a significant predictor of mobile SNS addiction.